ENHANCING LAND SERVICES BY INNOVATING APPLICATION FORM INFORMATION SYSTEMS - Pujiriyani, Dwi Wulan; Murti, Octadhea Kusuma; Nanda, Reza Mega; Utomo, Hafizh Faadhilah; Lili, Rasmaniful; Maharani, Vania; Qisto, Muhammad Al Baar; Putri, Sabrina Herlambang (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
This article aims to explain the implementation of community service through the creation of the SI-BAPER application and the benefits that the community derives from this community service activity. The steps for creating the Blanko Information System and Application Flow are as follows: 1) identify service types by grouping land services frequently requested by the public, 2) compile and visualize the application flow for each service, 3) upload PDF or Word files, flow diagrams, and application forms to Google Drive, 4) generate QR codes, 5) design stickers containing the SI-BAPER QR code, 6) affix the QR code at service counters or on notice boards at the Sukoharjo District Land Office and Village Offices, 7) conduct QR code testing with applicants/the public and village officials, and 8) explain the benefits of SI-BAPER to applicants/the public and village officials. The research results show that the SI-BAPER application is a strategic medium for bringing services closer to the village level. The inclusion paradigm is one of the important foundations for creating this application. In its implementation, the community feels greatly assisted by the presence of the SI- BAPER application. The follow-up to the creation of this application is to ensure that it can reach a wider range of village locations. The SI-BAPER application can also be replicated in other land offices as a form of facilitating easy land services. The SI-BAPER application needs to be continued to be synchronised with other public service applications available in the village.